The teacher’s pedagogical practice in high school: perceptions and narratives of young women (PerCursos, 2024)
The article discusses the pedagogical practices of high school teachers, based on the perceptions and narratives of young female students in their 3rd year. It starts with the premise that the pedagogical act is an interpersonal relationship between students and among students and teachers. The study suggests that the type of intersubjective communication that occurs within the classroom setting facilitates and ensures the conditions for the discovery of their future goals. The research follows a qualitative approach, using the principles of Social Phenomenology as its foundation. The methodology involved conducting 04 Narrative Interviews with students aged 16 to 18 years, who attend public schools in Belém/PA. These interviews were analyzed using the Documentary Method. The data analysis revealed that the pedagogical practice of high school teachers goes beyond being a space for academic learning and a means to engage with organized academic knowledge in different subjects. It also provides young women with the opportunity to explore and understand themselves better.
Keywords: pedagogical practices; high school; project of the future